Loss-of-Function GAS8 Mutations Cause Primary Ciliary Dyskinesia and Disrupt the Nexin-Dynein Regulatory Complex - Olbrich, Heike (Am J Hum Genet, 2015)
Multiciliated epithelial cells protect the upper and lower airways from chronic bacterial infections by moving mucus and debris outward. Congenital disorders of ciliary beating, referred to as primary ciliary dyskinesia (PCD), are characterized by deficient mucociliary clearance and severe, recurrent respiratory infections. Numerous genetic defects, most of which can be detected by transmission electron microscopy (TEM), are so far known to cause different abnormalities of the ciliary axoneme. However, some defects are not regularly discernable by TEM because the ciliary architecture of the axoneme remains preserved. This applies in particular to isolated defects of the nexin links, also known as the nexin-dynein regulatory complex (N-DRC), connecting the peripheral outer microtubular doublets. Immunofluorescence analyses of respiratory cells from PCD-affected individuals detected a N-DRC defect. Genome-wide exome sequence analyses identified recessive loss-of-function mutations in GAS8 encoding DRC4 in three independent PCD-affected families.